A comprehensive overview of exosomes in ovarian cancer: emerging biomarkers and therapeutic strategies - Lin Cheng; Shuying Wu; Kun Zhang; Yun'an Qing; Tianmin Xu (BMC, 2017)
Abstract Exosomes are nanoparticles(40-100 nm) secreted by most cells in the body, which can be isolated from several types of extracellular fluids. It has been shown that exosomes play a key role in intercellular communication and in transportation of genetic information. Emerging evidence shows that exosomes are mediators of metastasis in tumour cells, stromal cells and the extracellular matrix component through the shuttling of cargo, such as proteins, lipids, RNAs, double-stranded DNAs, non-transcribed RNAs, and microRNAs. This phenomenon has been indicated in both tumourigenesis and drug resistance. In this review, we introduce new methods of exosome extraction, focusing on the emerging role of exosomes in ovarian cancer, and discuss their potential clinical applications.